2013
DOI: 10.1155/2013/782847
|View full text |Cite
|
Sign up to set email alerts
|

Endophytic Actinomycetes: A Novel Source of Potential Acyl Homoserine Lactone Degrading Enzymes

Abstract: Several Gram-negative pathogenic bacteria employ N-acyl-L-homoserine lactone (HSL) quorum sensing (QS) system to control their virulence traits. Degradation of acyl-HSL signal molecules by quorum quenching enzyme (QQE) results in a loss of pathogenicity in QS-dependent organisms. The QQE activity of actinomycetes in rhizospheric soil and inside plant tissue was explored in order to obtain novel strains with high HSL-degrading activity. Among 344 rhizospheric and 132 endophytic isolates, 127 (36.9%) and 68 (51.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(16 citation statements)
references
References 43 publications
(47 reference statements)
1
15
0
Order By: Relevance
“…Extracts of endophyte bacteria Bacillus and Enterobacter from Pterocarpus showed AHLs degrading ability when applied on biosensor strains (Rajesh, Ravishankar, 2014). N-acyl-L-homoserine lactone acylase with specificity against medium and long chain AHLs was found in endophytic Streptomyces (Chankhamhaengdecha et al, 2013). AHL lactonase gene from Bacillus thuringiensis was introduced into endophytic Burkholderia which then was able to attenuate symptoms caused by pathogenic Burkholderia glumae in rice and Erwinia carotovora in potatoes (Cho et al, 2007).…”
Section: Occurrence and Diversity Of Bacterial Endophytes In Agricultmentioning
confidence: 99%
“…Extracts of endophyte bacteria Bacillus and Enterobacter from Pterocarpus showed AHLs degrading ability when applied on biosensor strains (Rajesh, Ravishankar, 2014). N-acyl-L-homoserine lactone acylase with specificity against medium and long chain AHLs was found in endophytic Streptomyces (Chankhamhaengdecha et al, 2013). AHL lactonase gene from Bacillus thuringiensis was introduced into endophytic Burkholderia which then was able to attenuate symptoms caused by pathogenic Burkholderia glumae in rice and Erwinia carotovora in potatoes (Cho et al, 2007).…”
Section: Occurrence and Diversity Of Bacterial Endophytes In Agricultmentioning
confidence: 99%
“…() and Chankhamhaengdecha et al . () have reported 36·9–66·0% bacterial strains isolated from rhizosphere and endophytic tissues of plants possess QQ activity. QQ enzymes of bacteria could be intracellular, cell bound or extracellular in nature (Romero et al .…”
Section: Resultsmentioning
confidence: 99%
“…Percentage of QQ bacteria isolated from rhizosphere and endophytic tissues of plants was earlier reported to be as low as 0Á8% (Newman et al 2008). In contrast, Chong et al (2012) and Chankhamhaengdecha et al (2013) have reported 36Á9-66Á0% bacterial strains isolated from rhizosphere and endophytic tissues of plants possess QQ activity. QQ enzymes of bacteria could be intracellular, cell bound or extracellular in nature (Romero et al 2008).…”
Section: Detection Of 3oh-pame Degradation By Endophytic Bacteriamentioning
confidence: 97%
“…B63 was only 360 pmol/h/mL. Similarly, leaf-associated strain LPC029, isolated from Gmelina arborea Roxb., has an AHL-degrading activity with 400 pmol/h/mL against 3OC6-HSL [40]. In the lactonase family, AiiA lactonase is the first and most well-studied group [11,41].…”
Section: Resultsmentioning
confidence: 99%